Router redundancy with enhanced vrrp for intelligent message routing - Saleem, H.M. (Springer Verlag, 2014)
Overlay query routing mechanism is a popular approach for query routing process in the distributed service and resource discovery. However it suffers from drawbacks such as escalated inter-ISP traffic and redundant traffic forwarding in the underlying IP layer. In order to avoid these problems we have proposed earlier that the overlay query routing process could be moved down to the IP layer with the help of intelligent message routing (IMR). The routers in the IP layer build a second routing table by mapping the content of the query messages with the target location of the services which is used for query forwarding. For such a system to be implemented in the Internet scale, high availability of routing service is vital. Employing Virtual Router Redundancy Protocol (VRRP) for redundancy takes care of classical route updates to the backup router. However, the service specific routing table which is specific for underlay query processing needs to be updated independent of VRRP. In this paper, we address the issue of applying router redundancy for IMR with enhanced VRRP which also can handle the redundancy for the service specific routing table. We have also analyzed the performance of routers with respect to the additional overhead taken due to service specific routing. Â© Springer International Publishing Switzerland 2014.